Channel‐Spanning Logjams and Reach‐Scale Hydraulic Resistance in Mountain Streams - Elizabeth Follett; Ellen Wohl (Geophysical Research Letters)
Abstract Logjams create an upstream backwater of deepened, slower water, locally reducing bed shear stress. We compared hydraulic impact of logjam series across 37 geomorphically diverse reaches of mountain streams observed over 11 years in the US Southern Rockies. To enable reach‐scale comparison of logjam structure and spacing, we identified the modeled best‐fit effective resistance coefficient minimizing difference between outflow exiting a 1D channel with logjams present, and the same model channel with elevated channel resistance. Effective resistance increased with ratio of jam upstream depth to depth without a logjam, ratio of backwater length to average spacing, and decreased for randomly distributed jams due to close spacing, which reduced backwater impact. An analytic approximation and boundaries for region of relative spacing with steepest increase in effective resistance are provided. Our results can assist in targeting interventions to areas where hydraulic impact is greatest, providing value for money in nature‐based solution design.